Promoting fintech financing for SME in S. Caucasian and Baltic States, during the Covid-19 global pandemic - Charaia, Vakhtang; Chochia, Archil; Lashkhi, Mariam (Business, Management and Economics Engineering, 2021)
Purpose – to analyse the digitalization trends in the Central Caucasian (Georgia, Azerbaijan and Armenia) and Baltic States with the aim of reducing a financial gap for the Small and Medium size Enterprises in Georgia, Azerbaijan and Armenia. Research methodology – comparative analysis between Baltic and Caucasian countries are made to analyse the basic positions and farther development opportunities for Georgia, Azerbaijan and Armenia. Findings of the given paper – while SME sector crucially important contributor to employment, diversification and productivity in any country of the world and especially in developing ones, they still face significant credit constraints through traditional credit providing institutions. However, the trend is changing and modern digital technologies from the fintech area are providing new alternatives, which already had been widely used in Baltic, but still are waiting their chance in Georgia, Azerbaijan and Armenia, with different level of progress and readiness. Research limitations – some statistical data does not exist for all six countries or were possible to obtain for different periods of time. Lack of academic literature on fintech in Caucasian countries. Practical implications – It can provide a useful perspective for researchers, academics, investors, investment managers, decision-makers, and scientists. Originality/Value – The paper analyses three advanced European Union member state’s (Lithuania, Latvia and Estonia) fintech positions and perspectives as a model of development for three developing Caucasian states (Georgia, Azerbaijan and Armenia).